2016
DOI: 10.1186/s40748-016-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section in sub-Saharan Africa

Abstract: Cesarean section is an essential maternal healthcare service. Its role in labor and delivery care in low- and middle-income countries is complex; in many low-resource settings it is underutilized in the most needy of populations and overused by the less needy, without clear methods to ensure that universal access is available. Additionally, even if universal access were available, it is not evident that these countries would have the capacity or the finances to appropriate meet demand for the procedure, or tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 53 publications
6
105
0
Order By: Relevance
“…The WHO established that CS is an essential procedure in the management of delivery, and recommended a rate of 5-15% of all births worldwide, based on the CS rates in countries with the lowest perinatal mortality and morbidity. 2 CS rates higher than 10% are not associated with a reduction in neonatal and maternal mortality rates. 5 Caesarean section rates vary depending on a multitude of factors, such as foetal, maternal and medical complications in pregnancy, and cultural attitudes towards CS.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The WHO established that CS is an essential procedure in the management of delivery, and recommended a rate of 5-15% of all births worldwide, based on the CS rates in countries with the lowest perinatal mortality and morbidity. 2 CS rates higher than 10% are not associated with a reduction in neonatal and maternal mortality rates. 5 Caesarean section rates vary depending on a multitude of factors, such as foetal, maternal and medical complications in pregnancy, and cultural attitudes towards CS.…”
Section: Introductionmentioning
confidence: 85%
“…12 In sub-Saharan Africa one third of elective CSs were done at a gestational age of less than 39 weeks. 2 The probability of antepartum stillbirth with an elective CS has been calculated at 0.08% at 38 weeks' gestation, and this figure increases to 0.34% at 41 weeks' gestation. 14 Infants delivered by pre-labour CS between 37 and 42 weeks gestational age were nearly seven times more likely to develop respiratory morbidity than infants who were delivered vaginally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This surgical procedure is viewed as one of the major World Health Organization's (WHO) medically suggested plan towards improving availability, accessibility, quality, and the use of services for the management and treatment of complications of pregnancy, labour, and delivery [3]. CS is also considered an essential treatment for antepartum haemorrhage, prolonged or obstructed labour, preeclampsia or eclampsia, and intrapartum foetal distress [4]. Nevertheless, a 2008 WHO survey of 373 facilities across 24 countries found that caesareans deliveries (CD) were associated with an increased risk of maternal mortality and serious outcomes for mothers and newborn infants, compared with spontaneous vaginal delivery (VD) [5].…”
Section: Introductionmentioning
confidence: 99%